Evaluation of the Effects of Actuator Line Force Smearing on Wind Turbines Near-Wake Development. Issue 1 (May 2021) - Cormier, Marion; Weihing, Pascal; Lutz, Thorsten
Abstract: In the present study, the effects of the actuator line force smearing on the predicted near-wake development of a model wind turbine are evaluated. To exclude the uncertainties related to the blade loads computation, the loads of a corresponding blade-resolving simulation are imposed. Three force projection functions are applied, which all radially scale with the local chord length: an isotropic Gauss force distribution, an anisotropic Gauss distribution with distinct projection widths in the chord and thickness directions, and a Gauss-Gumbel projection function which creates an airfoil-like force distribution in the chord direction. Comparisons with corresponding blade-resolving simulations and experimental results show a good agreement of the tip vortex core size, position and circulation. Comparison of the mid-wake instantaneous streamwise velocity with blade-resolving simulations shows a thinner vortex sheet and stronger effects of the trailed vortices in the actuator line simulation. Although the bound vortex shape scales with the projection function, no significant difference was observed in the resulting tip vortices and near-wake flow field between the three projection functions used. It is attributed to the similar projection width in the tip vortex region for all cases considered. With the chosen grid refinement in the tip vortex area and a smearing width that scales with the chord length, tip vortices that compare with high-resolution experiments and high-fidelity blade-resolving simulation could be generated with the actuator line approach.